ECO-FRIENDLY GREEN SOLVENT UV-SPECTROSCOPIC ANALYTICAL METHOD FOR ETRAVIRINE IN BULK DRUG AND DOSAGE FORM - Rajesh S. Chandrabose
A novel, green analytical method based on UV spectrophotometry has been developed for the practically water-insoluble antiviral drug etravirine in bulk and formulation. The method was validated for multiple parameters like linearity and range, precision, specificity, accuracy and robustness, as per ICH guidelines. The etravirine dissolved in 2 mM benzoic acid in 1 % w/V sodium lauryl sulphate was analyzed at 310 nm. The method demonstrated linearity in the 2.08- 14.56 (So(Bg mL-1 range with a correlation coefficient (r2 ) of 0.9997. The method accuracy was in the 100.73 to 101.88 % range. The method is green, eco-friendly, easy, specific, accurate and precise and requires relatively inexpensive instrumentation. The estimation of etravirine in bulk drug and tablet dosage form can be done by this new method.s